The complete mitochondrial genome of Xenophysogobio nudicorpa (Teleostei, Cyprinidae, Gobiobotinae). (3rd May 2016) - He, Bin; Liu, Ya; Lai, Jiansheng; Zhou, Jian; Chen, Yeyu; Du, Jun
Abstract: Xenophysogobio nudicorpa is one member of the genus containing two species only, which is a specialized lineage of gobiobotine fishes. In this study, we provide the first mitochondrial genome of X. nudicorpa . The complete mitochondrial genome of X. nudicorpa is 16, 616 bp in length, containing 13 protein-coding genes, two rRNA genes (12 S and 16 S rRNA), 22 tRNA genes and a noncoding control region (D-loop). The gene nucleotide composition of X. nudicorpa is 30.5% A, 26.0% T, 16.8% C and 26.7% G, with a slight AT bias of 56.5%. The complete mitochondrial genome of X. nudicorpa would be useful for further studies on genetic diversity and molecular phylogenetic relationship of the subfamily Gobiobotinae.